Now hiring : a manager's guide to employing applicants with a criminal history - Young, Nicole Jones (Emerald Publishing Limited, 2022)
Now Hiring allows readers to consider their individual biases - as well as organizational employment practices and processes - and assess how these factors may be altered to increase hiring for individuals with a criminal history, prompting conversations surrounding current hiring systems.